2010
DOI: 10.1007/s10620-010-1484-y
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Liberated from Carbon Monoxide-Releasing Molecule Exerts an Anti-inflammatory Effect on Dextran Sulfate Sodium-Induced Colitis in Mice

Abstract: CORM-liberated CO significantly inhibited inflammatory response in murine colitis by inhibition of cytokine production in the colonic epithelium. These results suggest that CO could become a new therapeutic molecule for inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 60 publications
2
39
0
Order By: Relevance
“…[5][6][7][8] The heme oxygenase (HO) group of enzymes, of which HO-1 is inducible in immune cells, mediate heme degradation, generating equimolar amounts of iron, biliverdin, and CO. We and others have demonstrated that the HO-1/CO pathway can regulate intestinal inflammation in experimental models of acute and chronic intestinal inflammation. [9][10][11][12][13] Indeed, in our work, anti-inflammatory effects of CO required the induction of HO- 12 Our work leads to a model where, in the local microenvironment of the intestine, CO and HO-1 are components of an evolutionarily conserved homeostatic pathway modulated in health and disease by cross-talk between the microbiota and the mucosal immune compartment.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…[5][6][7][8] The heme oxygenase (HO) group of enzymes, of which HO-1 is inducible in immune cells, mediate heme degradation, generating equimolar amounts of iron, biliverdin, and CO. We and others have demonstrated that the HO-1/CO pathway can regulate intestinal inflammation in experimental models of acute and chronic intestinal inflammation. [9][10][11][12][13] Indeed, in our work, anti-inflammatory effects of CO required the induction of HO- 12 Our work leads to a model where, in the local microenvironment of the intestine, CO and HO-1 are components of an evolutionarily conserved homeostatic pathway modulated in health and disease by cross-talk between the microbiota and the mucosal immune compartment.…”
Section: Introductionmentioning
confidence: 67%
“…[9][10][11]14 Importantly, CO exposure and HO-1 induction have been shown to ameliorate colitis in numerous experimental models of IBD with different immunopathogeneses, highlighting the importance of this pathway as a homeostatic checkpoint in intestinal immune responses. [9][10][11]13,14,21 Using Il10 −/− mice as a model of microbiota dependent, IL-12/23-mediated chronic intestinal inflammation, we demonstrated that exposure to CO ameliorated colitis in an HO-1 dependent manner.…”
Section: Ho-1/co Ameliorate Colitis Through Altered Cytokine Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental acute colitis was induced by treatment with 2.0% DSS (molecular weight 1,000-9,000, Lot SDR4219; Wako Pure Chemical Industries, Osaka, Japan) in drinking water for 7 days, as reported previously (26,27). Mice were sacrificed under anesthesia 7 days after DSS treatment, and the colons were removed for macroscopic and histological examination.…”
Section: Induction Of Colitis By Dssmentioning
confidence: 99%
“…DAI was determined by scoring changes in animal weight, occult blood positivity, gross bleeding and stool consistency, as described previously (26,28,29). We used 5 grades of weight loss (0, no loss or weight gain; 1, 1-5% loss; 2, 5-10% loss; 3, 10-20% loss; 4, >20% loss), 3 grades of stool consistency (0, normal; 2, loose; and 4, diarrhea), and 3 grades of occult blood (0, negative; 2, occult blood-positive; and 4, gross bleeding) based on previous studies (26,27). After determining DAI, the mice were sacrificed, and the entire colon was removed from the cecum to the anus, and colon length was measured as an indirect marker of inflammation.…”
Section: Induction Of Colitis By Dssmentioning
confidence: 99%